2014
DOI: 10.1186/1472-6963-14-227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multi-pronged intervention to improve access to safe abortion care in two districts in Jharkhand

Abstract: BackgroundDespite the adoption of the Medical Termination of Pregnancy Act in 1972, access to safe abortion services remains limited in India. Awareness of the legality of abortion also remains low, leading many women to seek services outside the health system. Medical abortion (MA) is an option that has the potential to expand access to safe abortion services. A multi-pronged intervention covering a population of 161,000 in 253 villages in the Silli and Khunti blocks of Jharkhand was conducted between 2007 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…Women who had an induced abortion in the facility had a much higher acceptance of any method, especially of long-acting methods or sterilization, than women seeking care for postabortion complications. These findings are in line with earlier studies in India (Banerjee et al 2014) that show providers' disinclination to offer contraception, and more specifically long-acting methods, immediately after postabortion care, primarily because of fear of infection (Banerjee and Manning 2010).…”
Section: Diagnosis: Induced Abortion and Postabortion Caresupporting
confidence: 90%
“…Women who had an induced abortion in the facility had a much higher acceptance of any method, especially of long-acting methods or sterilization, than women seeking care for postabortion complications. These findings are in line with earlier studies in India (Banerjee et al 2014) that show providers' disinclination to offer contraception, and more specifically long-acting methods, immediately after postabortion care, primarily because of fear of infection (Banerjee and Manning 2010).…”
Section: Diagnosis: Induced Abortion and Postabortion Caresupporting
confidence: 90%
“…There was a shift towards women seeking care earlier in pregnancy. 15 The demonstrated success of this intervention shows that with the necessary modifications there is a potential for replication on a larger scale. Although our study is restricted to one public hospital, it can serve as a starting point for larger prospective studies to identify target groups which should be the focus of intended counseling.…”
Section: Discussionmentioning
confidence: 97%
“…Study showed that higher level of exposure to messages related to abortion resulted in more accurate knowledge (18). Multi-pronged intervention through BCC in India was found to improve access to safe abortion care and this can be replicated in similar settings (19).…”
Section: Introductionmentioning
confidence: 91%
“…In current study, after BCC intervention, there was a measurable change in knowledge and perceptions regarding different aspects of reproductive health behavior related to abortion. Literature from South Asian region has demonstrated a strong relationship between exposure to health education messages on abortion and on the level of knowledge in a meaningful way (18,19). Socio-economic issues, limiting parity are found to be main reasons for seeking abortion and women often have more than one reason for deciding for abortion.…”
mentioning
confidence: 99%